Effectiveness of a Proposed Program Based on Semi-Athletics Games in Developing Emotional Intelligence in Camp Children aged between 9 and 11 years old - Kouadri Rana; Abdelli Fateh (My University, 2022)
The study aims to know the effectiveness of a proposed program based on semi-athletics games in the development of the emotional intelligence in camp children aged between 9 and 11 years old. This research is based on an experimental approach with an experimental design which contains two groups of individuals: the experimental group and the control group, where the sample included 30 children from Karma camp, Boumerdes using Daniel Golman's emotional intelligence scale. After confirming its psychometric properties, the data are also treated by the social sciences statistical software package SPSS25. The results indicate that the proposed program based on semi sports games is effective in developing emotional intelligence in the camp's children. effectiveness, emotional intelligence, semi-athletics games, summer camps.